Identification Latent Tuberculosis Infection In Dialysis Patients : A Systematic Review - hamidah retno wardani (The Indonesian Journal of Health Science, 2021)
LTBI infection is a dormant condition of the tuberculosis organism. It is often defined as a condition without symptom with the tuberculosis organisms in the lung tissue, without clinical signs, or radiological signs. LTBI can become active TB in immunosuppressed hosts caused by comorbid disease or medical therapy such as patients with end-stage renal disease. Screening TB infection using examination tests such as the TST, QFT-G, and complete treatment in dialysis patients can avoid the progression of LTBI into active-TB. This research identified the incidence of LTBI in dialysis patients using the two-step TST and QFT-G. A Systematic Review study to identification the incidence of LTBI in dialysis patients using the Prefered Reporting Items for Systematic Review and Meta-analysis protocol. Derived from 67 related articles and obtained 4 articles using the Randomized Control Trial (RCT). Totally 516 dialysis patients and the study showed that the incidence of LTBI using two-step TST (cut off ≥ 10 mm) and QFT-G (≥ 35 IU/ml) showed that TST /QFT-G positive 68 patients (18.47%), only positive TST 22 patients (5.97 %), only positive QFT-G 77 patients (20.92%). This study showed that a high incidence of LTBI in dialysis patients. Early detection and complete treatment of LTBI should be performed in dialysis patients to avoid the reactivation of LTBI into active TB.